2017
DOI: 10.24331/ijere.327470
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Model of Intercultural Communication Competence (ICC) in Malaysian Context

Abstract: The basic determination for this paper is to throw light on the culture general models of intercultural communication competence (ICC). Furthermore, to propose a culture general model for Malaysian context in the presence of religiosity. It is suggested by the previous researchers to refine these models by adding variables in them. Ministry of Higher Education of Malaysia is hosting huge number of international students in their institutions and have plans to host maximum from the whole world. Religion is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Later, these factors were addressed on the students from multiple cultures in different versions of IMICC (Arasaratnam and Banerjee, 2011; Arasaratnam et al , 2010a). A study by Nadeem et al (2017) argued that there are multiple versions of IMICC, and it is hard to find the application of these models in other cultural contexts to ensure its universal application. Furthermore, the study strongly suggested to add other culture-general contributors of ICC in IMICC and readdress IMICC in the Malaysian context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, these factors were addressed on the students from multiple cultures in different versions of IMICC (Arasaratnam and Banerjee, 2011; Arasaratnam et al , 2010a). A study by Nadeem et al (2017) argued that there are multiple versions of IMICC, and it is hard to find the application of these models in other cultural contexts to ensure its universal application. Furthermore, the study strongly suggested to add other culture-general contributors of ICC in IMICC and readdress IMICC in the Malaysian context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the importance of religion cannot be ignored in the context of Malaysia, and it is crucial to examine the relationship between religion and ICC empirically. Responding to this call, this study re-examines and refines IMICC model (Arasaratnam & Banerjee, 2011;Nadeem et al, 2020bNadeem et al, , 2021 with religiosity (as a moderating variable) and aims to test it in the Malaysian context (Nadeem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact, it is evident from the recent researches that existence of a relationship among potential influencers (such as, empathy and attitudes) of ICC [Arasaratnam (2016); Deardorff (2009Deardorff ( ), (2015]. Even though majority of these concepttualizations have emerged from the western context, it is considered worthy to investigate the association of different contributors of ICC from the nonwestern context of Malaysia [Nadeem et al (2017a)].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from the existing studies of intercultural communication that students possess abilities such as empathy and attitude towards other cultures (ATOC) that help them to be competent in intercultural interactions [Arasaratnam et al (2010a[Arasaratnam et al ( , 2010b]. On the other side, there are some potential researchers [Deardorff et al (2017); Dunne (2013); Nadeem et al (2017a)] who strongly recommend to further explore the relationship between empathy and ATOC of the individuals during their intercultural encounters. Therefore, this current study targets to readdress the influence of empathy on the ATOC of the international students from the new cultural context of Malaysia.…”
Section: Introductionmentioning
confidence: 99%